A Study on the Historical Evolution, Value, and Inheritance Innovation of Farming and Weaving Pictures - Jia Luo (Al-Qanṭara, 2023)
Farming and Weaving Pictures show farming and weaving scenes in ancient China, providing picture materials for studying agriculture, folk customs, and art in various dynasties. This paper employed the literature review and iconography to study the themes and images of several editions of the Farming and Weaving Pictures by Lou Shu of the Song Dynasty, Cheng Qi of the Yuan Dynasty, Kuang Fan of the Ming Dynasty, and Jiao Bingzhen of the Qing Dynasty, thus describing and analyzing the historical evolution, characteristic styles, and values of these pictures. In addition, it elaborated the approaches for the protection and inheritance innovation of these pictures based on digital technologies, in hope of providing a reference for the protection and inheritance innovation of tangible cultural heritage. Psychological research shows that more than 80% of learning occurs via our visual memory system. Compared with characters, images are more readable and visually attractive, so they are easier to be accepted by the public. Ancient people knew this fact early. Therefore, all sorts of images were used to record and introduce agriculture in brilliant Chinese history and culture. Farming and Weaving Pictures are one of the most representative works on agricultural practices among image materials. This paper studied Farming and Weaving Pictures drawn by Lou Shu and other related pictures.